2022
DOI: 10.1111/nhs.12938
|View full text |Cite
|
Sign up to set email alerts
|

Identification of research priorities of radiography science: A modified Delphi study in Europe

Abstract: Radiography science is a new discipline among health sciences. It is a discipline that investigates phenomena in medical imaging, radiation therapy, and nuclear medicine. It has merged from the need to provide research evidence to support these services. The domain of the discipline needs clarification and more research should be focused on its paradigmatic issues. Radiography research priorities have been previously charted on a national level in different countries but the viewpoint has been that of the need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
(78 reference statements)
0
6
0
Order By: Relevance
“…Coupled with the strategy, funding, and research culture is the need to identify contextual research priorities. For example, studies by T€ ornroos, et al 40 and The College of Radiographers 41 identified several research priorities for Radiography within the European and UK contexts. These were classified into the following broad categories: radiographers' profession, clinical practice in radiography, safe and high-quality use of radiation, technology in radiography, discipline of radiography science and leadership and management.…”
Section: Identify Research Prioritiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Coupled with the strategy, funding, and research culture is the need to identify contextual research priorities. For example, studies by T€ ornroos, et al 40 and The College of Radiographers 41 identified several research priorities for Radiography within the European and UK contexts. These were classified into the following broad categories: radiographers' profession, clinical practice in radiography, safe and high-quality use of radiation, technology in radiography, discipline of radiography science and leadership and management.…”
Section: Identify Research Prioritiesmentioning
confidence: 99%
“…Coupled with the strategy, funding, and research culture is the need to identify contextual research priorities. For example, studies by Törnroos, et al 40 . and The College of Radiographers 41 identified several research priorities for Radiography within the European and UK contexts.…”
Section: Considerations To Enhance Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on Sanna Törnroos et al, the research priorities of radiography science in Europe are related to the radiographers' profession, clinical practice, and the safe,high-quality use of radiation and technology for medical imaging [ 8 ]. The research priorities among Norwegian radiation therapists (RTs) focus on enhancing professional practice, specifically in the areas of new techniques and competence [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…1,91,92 It is notable that awareness about the importance of patient-centred counselling has increased, 93 with patient-centred care and evidence-based practices for improving the quality in clinical practice recently identified as research priorities for radiography science. 94 A total of five previous studies have analysed CCTA-related anxiety (Table 2). Notably, 50e74% of patients experienced anxiety before the CCTA.…”
Section: Introductionmentioning
confidence: 99%